a study on metaphoric expressions in english tourism advertisements - Trà,Thị Doãn Dung; Trần Văn Phước (ĐHĐN : ĐHĐN., 2014)
This study mainly investigates how to use the syntactic and semantic features of metaphoric expressions in English tourism advertisements. The study collected 150 samples from 55 English websites then analyzed on syntactic and semantic aspects basing on the basic theory of M.A.K. Halliday (1985) with his famous work: „An Introduction to Functional Grammar‟. The finding shows that metaphoric expressions on noun phrases, verb phrases, and adjective phrases are mostly expressed. And in semantic site, ranges of history, beauty and life style are used most frequently, and this gives us more view and knowledge about tourist destinations. With findings above, semantic and syntactic features of metaphor are partly proposed to contribute to better the teaching and learning of English as a foreign language, especially to better the learners who are aware of translating and working in tourism industry.
Master thesis in social sciences and humanities
Keywords: metaphoric expressions in english tourism advertisements; metaphoric expressions -- tourism advertisements